Um olhar surdo sobre políticas linguísticas na Universidade Federal do Tocantins - Felipe de Almeida Coura (2021)
Discussions about language policies, involving sign languages, are somewhat unfamiliar to those who research and develop language policies in general (REAGAN, 2010). At the Federal University of Tocantins (UFT) it does not happen any differently. In this way, in many cases, the power relationship that the Portuguese language exercises over Libras may undermine the guarantee of linguistic rights for the deaf. However, the experiences that the deaf have brought over the years and a new look at language policies in higher education, may point to significant possibilities for this situation. This research aims to analyze the language policies of the UFT that relate to the deaf. In this sense, using characteristics of the Ethnography of Language Planning and Policy and the Narrative Interview, this study also intends (1) to identify the language policies for the deaf at national and local level; (2) to present and interpret the narratives of deaf students and professors at UFT about their experiences with the Portuguese Language and Libras at the institution and (3) to propose reflections and suggestions for implementing language policies at UFT based on the experiences of the participants. The theoretical framework contemplates the understanding of language policies from McCarty (2011) and Tollefson (1991; 2013), in addition to addressing discussions of the relationship between linguistic policies and sign languages based on De Meulder (2015a; 2015b), De Meulder et al (2019), De Meulder and Murray (2017), and others. The research points out, among other results, that (i) the construction of explicit and implicit language policies in the Letras-Libras undergraduate course and in the Graduate Program in Letters at the Porto Nacional campus may point out alternatives for modifications and implementations for the entire UFT; (ii) the deaf participants in the research are aware of their rights, they know how some points may be modified in order to favor language policies that adopt a deaf perspective, however they perceive the challenges of an “education of their surroundings to respect the difference” (MAHER, 2007, p. 257). Apparently, this is a greater challenge than those that refer to the reading and writing of the Portuguese language, for example; moreover, it is clear that (iii) Ethnography of Language Planning Policy may continue to contribute to research at UFT that favors different ways of creating, interpreting and appropriating language policies.